2007
DOI: 10.2355/isijinternational.47.1527
|View full text |Cite
|
Sign up to set email alerts
|

Variant Selection of Reversed Austenite in Lath Martensite

Abstract: Fig. 3. Bright field (a) and dark field TEM image (b) of 13Cr-6Ni steel partially reversion treated at 913 K for 1.8 ks. The direction of the incident beam is roughly ͗111͘aЈ and ͗110͘g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 19 publications
4
78
1
Order By: Relevance
“…However, it is known that reversed austenite tends to nucleate at LBs in martensitic and bainitic steels during heat treatment in (ferriteϩaustenite) two phase region. [2][3][4][5][6] Authors also confirmed in the previous study that the reversed austenite preferentially nucleated at LBs rather than prior austenite grain boundaries (PAGBs) in 13%Cr-6%Ni martensitic stainless steel reversion-treated at 913 K. 7) On the contrary, some researchers reported that the nucleation behavior of austenite was influenced by the heating rate in low carbon steels; acicular austenite grains were frequently formed within a prior austenite grain under a low heating rate, while the granular ones tended to be formed mainly on PAGBs when the heating rate was increased. [2][3][4][5][6] This result suggests that the shape and nucleation site of reversed austenite would depend on the temperature at which the nucleation occurs.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, it is known that reversed austenite tends to nucleate at LBs in martensitic and bainitic steels during heat treatment in (ferriteϩaustenite) two phase region. [2][3][4][5][6] Authors also confirmed in the previous study that the reversed austenite preferentially nucleated at LBs rather than prior austenite grain boundaries (PAGBs) in 13%Cr-6%Ni martensitic stainless steel reversion-treated at 913 K. 7) On the contrary, some researchers reported that the nucleation behavior of austenite was influenced by the heating rate in low carbon steels; acicular austenite grains were frequently formed within a prior austenite grain under a low heating rate, while the granular ones tended to be formed mainly on PAGBs when the heating rate was increased. [2][3][4][5][6] This result suggests that the shape and nucleation site of reversed austenite would depend on the temperature at which the nucleation occurs.…”
Section: Introductionsupporting
confidence: 67%
“…The data obtained by the EBSD method was analyzed by the orientation imaging microscopy (OIM TM ) system. Volume fraction of austenite phase was measured by thermodilatometry method 7) for during heat treatment and the saturation-magnetization measurement 8) for after cooling to ambient temperature. The generation of elastic strain energy by formation of an austenite nucleus was simulated by using the general-produced finite element (FEM) method analysis code MARC2005.…”
Section: Methodsmentioning
confidence: 99%
“…So the intercritical annealing was applied to get large amount of austenite due to austenite reverted transformation (ART) from martensite, which was named ART-annealing. [8][9][10] Recently, H. L. Yi, et al reported the significant results about ferrite/austenite duplex C-Mn steels, which had excellent mechanical properties with ultimate strength 900 MPa and total elongation 28%.…”
Section: Introductionmentioning
confidence: 99%
“…Globular austenite tends to nucleate at original austenite grain boundaries or inside the lathes with substrate of precipitates, thus disintegrate the original austenite grain and lead to grain refinement 11,13,16,18) In the "acicular" mechanism, acicular austenite nucleates at lath boundaries and has a K-S orientation relationship with the matrix, and recovery of original austenite grain happens after phase transformation. 11,13,14,16,18) However, there is still a demand for more comprehensive investigations for the formation mechanism of the reversed austenite, since possible factors that affect the nucleation and growth behaviors of reversed austenite are complicated, for instance, Ni/Cr ratio, 6) C content, 2) heating rate, 3) intercritical annealing temperature 5) and so on. A lot of work has been done to investigate the reversed austenite growth behavior in Fe-Cr-Ni alloys.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,11,[13][14][15][16][18][19][20][21] It is commonly accepted that there are two kinds of reversed austenite formation mechanisms, namely "acicular" and "globular" mechanisms, respectively. Globular austenite tends to nucleate at original austenite grain boundaries or inside the lathes with substrate of precipitates, thus disintegrate the original austenite grain and lead to grain refinement 11,13,16,18) In the "acicular" mechanism, acicular austenite nucleates at lath boundaries and has a K-S orientation relationship with the matrix, and recovery of original austenite grain happens after phase transformation.…”
Section: Introductionmentioning
confidence: 99%